Debt burden and Donor Fatigue: Managing Economic Challenges (African Journal of Public Administration & Management, 2026)
This study explored the dual challenges of debt burden and donor fatigue and their implications for managing economic development in Sub-Saharan Africa (SSA). It assessed how rising external debt and declining aid commitments constrain sustainable economic growth and identifies policy options to strengthen financial resilience. Using macroeconomic data from the World Bank, International Monetary Fund (IMF), and Organisation for Economic Co-operation and Development (OECD) covering the period 2010–2024, the analysis focuses on debt levels, aid flows, fiscal balances, and GDP growth rates. Drawing on Dependency Theory and Debt Overhang Theory, the study explains how structural dependence on external financing and excessive indebtedness suppress economic performance.